Time Course of Attentional Biases Toward Body Shapes in Women Who Are Overweight or Obese - Lyu, Zhenyong; Zheng, Panpan; Wang, Zhan (Cognitive therapy and research, 2019)
Although attentional bias toward body-related stimuli has been implicated as a vulnerability factor for body image disturbances, the time course of attentional biases toward body shapes in women who are overweight or obese is not clear. Using a dot-probe task and a between-subjects design, we assessed attentional biases (including facilitated attention, delayed disengagement, and avoidance) toward fat and thin body images in women who were overweight or obese (body mass index, BMI ≥ 25 kg/m 2 ; n = 25) and normal-weight controls (BMI < 25 kg/m 2 ; n = 25). Three stimulus presentation times were used: 100 ms, 500 ms, and 2000 ms. Women who were overweight or obese reported a stronger relative preference for Thin over Neutral images. All participants showed attentional bias toward thin body images in the initial orientation (100 ms) and later avoidance (2000 ms) stage, whereas only the women who were overweight or obese showed a bias toward fat body-related images when displayed for 500 ms, indicating difficulty disengaging from fat body-related stimuli. Slower attentional disengagement from fat body stimuli might be a cognitive marker for body image disturbance in women who are overweight or obese.